ETHICAL AND DEONTOLOGICAL EDUCATION OF ALLERGOLOGISTS IN THE PERIOD OF NEW UZBEKISTAN - ASALOV GIYOSIDDIN (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Relevance. Among the problems of theoretical medicine and practical healthcare in Uzbekistan, communicative competence and ethical and deontological education have not yet taken their proper place, they have turned out to be secondary (2,3). If the insufficient professional competence of a medical worker cannot always be recognized by the patient, then his moral character is exposed without difficulty. This leads to a negative society and does not contribute to the successful solution of the important tasks facing independent Uzbekistan. The curricula of universities in allergology do not sufficiently cover knowledge of psychology, philosophy and deontology, future allergists do not receive the necessary knowledge in this field and therefore do not evaluate the actions of patients. The lack of interest of the department in this important field of medical education worsens the quality of the medical worker. (1.4). Such necessary moral qualities as empathy, mercy, sociability, and smiling should be the daily behavior of a medical worker. (2.5). Communication problems are a complex, multifaceted process of communication between people, including the exchange of information, perception and understanding, and often the assessment of another person’s behavior. Interpersonal communication, most often dialogical, is an indispensable component of professional medical activity. Intelligence, a sense of contact, the ability to listen and direct the patient’s train of thought in the right direction, as well as other qualities have always been inherent in the best part of tabibs and national doctors like ibn Sino, ar-Roziy, Hakim Yusufiy, Zohidkhon ibn Vosithon Shoshi, academician- pediatrician S.Shamsieva, academician –pediatric surgeon A.Sulaimonova, professor therapist E.Kasimova, R.Alavia, A.Zohidia. (4,5).